Penilaian Risiko Keselamatan Dan Kesehatan Kerja (K3) Pekerjaan Reparasi Kapal Pada PT Dewa Ruci Agung Dengan Menggunakan Metode Hazard Identification And Risk Assesment And Determining Control (HIRADC) - Rexi Ilham A; Minto Basuki (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
This study aims to identify, analyze and mitigate the risks of work accidents at PT Dewa Ruci Agung. Occupational Health and Safety (K3) is very important to be implemented by every company. Prevention of work accidents can be done by knowing the existing risks, one of which is through the Hazard Identification, Risk Assessment and Determining Control (HIRADC) method. The data collection method used in this study uses primary and secondary data. From the results of the study it was found that there were 15 potential hazard risks including the Lifting Process of moving blocks/goods using a crane, the Cutting Process lifting material and placing it on the cutting machine, preparing the cutting machine, the Grinding Process lifting material and placing it in the grinding area, preparing grinding tools, Fitting Process and Working at Height plate installation process, Main Engine (ME) Overhaul Process, New metal seat removal process (ME) using manual tools, Removal process (ME) with Chain block, Cylinder liner (ME) removal process with chain block, Process Welding, Sandblasting and Painting Process, Zinc Anode Process, B3 Waste Disposal Process. Based on the results of the risk analysis, risk identification is then carried out using the HIRADC method which is most likely to reduce the level of risk severity. The risk identification proposed by the researcher is that it is recommended that every worker carrying out the task wear PPE in accordance with the provisions given by the company and the person in charge of the company's K3. So that unwanted events do not occur. Always check tools and Personal Protective Equipment (PPE) regarding their eligibility for worker safety.